The Regulation Impact of Foreign Ownership on the Cooperation Projects Air Transportation - I Dewa Gede Palguna; Anak Agung Gede Duwira Hadi Santosa; Made Cinthya Puspita Shara; Alia Yofira Karunian (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2024)
This study aims to identify, locate, and analyze constitutional issues regarding the impact of foreign capital ownership above 50% (fifty percent) in government-business cooperation projects, particularly in the area of public interest projects involving air transportation infrastructure. This normative research examines legal texts, mainly primary and secondary legal materials. This research found that, first, the changes in the Presidential Regulation regarding foreign investment in the field of public interest, such as airport services, were incompatible with the Constitution. The changes abolished the maximum percentage limit of foreign investment regulated in the previous provisions so that currently, foreign investment may carry out Government Cooperation with Business Entities on air transportation infrastructure projects without a percentage limit. Second, based on the Indonesian Constitution, ownership of air transportation should be under the state's authority, learning from China, which excessively applies foreign investors in the air transportation sector, causing consumer welfare to be affected by very high airplane ticket prices.